Gender Differences of Serum Leptin Hormone Levels in Iraqi Population - I.Mustafa, Besma (Iraqi Journal of Pharmaceutical Sciences, 2017)
To evaluate and compare serum Leptin hormone level between Iraqi male & female and the relation between this hormone & BMI in these two groups. A total of 44 normal male & female subjects were included in this study Group 1 : 22 female , Group 2 : 22 male. Serum Leptin hormone ,BMI &fasting blood glucose were measured for both groups. Serum Leptin level in group 1 was (8.82 + 2.9 μg/L) where as in group 2 it was (4.65 + 3.2 μg/L) . These changes were statistically significant. Fasting blood glucose levels were technically within the normal value (116.43 + 3.4mg /dl) for group 1 & (118.52 + 2.9 mg /dl) for group 2 . BMI levels were comparable in both groups during the study, with slight elevation in group 1 [ 24 + 1.73 kg /m2 for group 1 & 23 + 1.98 kg /m2for group 2 ] which within the acceptable limit as far as safety concern. Leptin, an adipocyte-derived hormone known to play an important role in body-weight regulation, the result of this study shows that Leptin is presented differentially in Iraqi men and women ; in which it is significantly higher in women than in men serum . These observations are potentially important for the understanding of differences between men and women in regulation of food intake, weight gain, and body fat distribution.The relation between Leptin & the BMI in male and female in this study may open another approach for this hormone to be involved in –fertility & in pubertal development.